Huaier Extract Inhibits Prostate Cancer Growth via Targeting AR/AR-V7 Pathway - Liu, Zhengfang; Liu, Cheng; Yan, Keqiang; Liu, Jikai; Fang, Zhiqing; Fan, Yidong (Frontiers in Oncology, 2021)
The androgen receptor (AR) plays a pivotal role in prostatic carcinogenesis, and it also affects the transition from hormone sensitive prostate cancer (HSPC) to castration-resistant prostate cancer (CRPC). Particularly, the persistent activation of the androgen receptor and the appearance of androgen receptor splicing variant 7 (AR-V7), could partly explain the failure of androgen deprivation therapy (ADT). In the present study, we reported that huaier extract, derived from officinal fungi, has potent antiproliferative effects in both HSPC and CRPC cells. Mechanistically, huaier extract downregulated both full length AR (AR-FL) and AR-V7 mRNA levels via targeting the SET and MYND domain-containing protein 3 (SMYD3) signaling pathway. Huaier extract also enhanced proteasome-mediated protein degradation of AR-FL and AR-V7 by downregulating proteasome-associated deubiquitinase ubiquitin-specific protease 14 (USP14). Furthermore, huaier extract inhibited AR-FL/AR-V7 transcriptional activity and their nuclear translocation. More importantly, our data demonstrated that huaier extract could re-sensitize enzalutamide-resistant prostate cancer cells to enzalutamide treatment in vitro and vivo models. Our work revealed that huaier extract could be effective for treatment of prostate cancer either as monotherapy or in combination with enzalutamide.